PENINGKATAN PRESTASI BELAJAR IPS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION PADA SISWA KELAS IX A SMP NEGERI 21 KOTA JAMBI - Boy Surau (Jurnal Ilmiah Dikdaya, 2017)
This Classroom Action Research is conducted on student grade IX Private Junior High School of Adhyaksa which is 34 students and consist of 15 male and 19 female. This research is Started from August to November 2014. The fact that found in learning social science at grade IX Private Junior High School of Adhyaksa, that low student motivation, student still depend on teacher and still conventional learning. It is caused that 15 students of 34 students can’t get minimum passing grade creteria. Based on that caused the researcher urgent to do coorperative Learning group investigation type to increase student motivation learning to achieve social science learning according to minimum passing grade criteria which is issued by School. The succession which researcher target in this research is to get the minimum passing grade criteria. After doing at the end of second cycle the researcher got target it, because the teacher and students which applied coorperative Learning investigation group type that got a good score. The researcher conducted well to apply action by using coorperative Learning investigation group type on student motivation. There is significant increase of studentss achievement on second cycle, but on first cycle student still depend on teacher and afraid to express it, but it is done on second cycle. Keywords : Learning Model, coorperative, group investigation, Learning achievement.